Arsenic efflux governed by the arsenic resistance determinant of Staphylococcus aureus plasmid pI258. - Bröer, S (1993)
The arsenic resistance operon of Staphylococcus aureus plasmid pI258 determined lowered net cellular uptake of 73As by an active efflux mechanism. Arsenite was exported from the cells; intracellular arsenate was first reduced to arsenite and then transported out of the cells. Resistant cells showed lower accumulation of 73As originating from both arsenate and arsenite. Active efflux from cells loaded with arsenite required the presence of the plasmid-determined arsB gene. Efflux of arsenic originating as arsenate required the presence of the arsC gene and occurred more rapidly with the addition of arsB. Inhibitor studies with S. aureus loaded with arsenite showed that arsenite efflux was energy dependent and appeared to be driven by the membrane potential. With cells loaded with 73AsO4(3-), a requirement for ATP for energy was observed, leading to the conclusion that ATP was required for arsenate reduction. When the staphylococcal arsenic resistance determinant was cloned into Escherichia coli, lowered accumulation of arsenate and arsenite and 73As efflux from cells loaded with arsenate were also found. Cloning of the E. coli plasmid R773 arsA gene (the determinant of the arsenite-dependent ATPase) in trans to the S. aureus gene arsB resulted in increased resistance to arsenite.